Use of Constructed-Response Questions to Support Learning of Cell Biology during Lectures - Foong May Yeong (American Society for Microbiology, 2015)
The use of class-response systems such as the Clickers to promote active-learning during lectures has been wide-spread. However, the often-used MCQ format in class activities as well as in assessments for large classes might lower students’ expectations and attitudes towards learning. Here, I describe my experience converting MCQs to constructed-response questions for in-class learning activities by removing cues from the MCQs. From the responses submitted, students seemed capable of providing answers without the need for cues. Using class-response systems such as Socrative for such constructed-response questions could be useful to challenge students to express their ideas in their own words. Moreover, by constructing their own answers, mis-conceptions could be revealed and corrected in a timely manner.